2010
DOI: 10.1038/ijo.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency for proprotein convertase subtilisin/kexin type 2 in mice is associated with decreased adiposity and protection from dietary fat-induced body weight gain

Abstract: Background: Proprotein convertase subtilisin/xexin type 2 (PCSK2) is an endoproteinase responsible for proteolytic activation of a number of precursors to active neuropeptides and peptide hormones, known to influence glucose homeostasis, food intake and ultimately body mass. In this study, we examined the consequences of PCSK2 deficiency on these phenotypic traits. Study Design: Weight gain with age under diets of different fat contents was monitored. White adipose tissue (WAT) and muscle masses were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In addition, they exhibit fasting hypoglycaemia, reduced blood glucose and reduced circulating glucagon during intraperitoneal glucose tolerance testing. Processing of proglucagon and proinsulin is severely impaired in these mice [26,27]. Furthermore, supporting the notion of PC2 effects on proglucagon processing, we observed that the PCSK2 variant was associated with lower glucagon levels in hyperglycaemic individuals.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, they exhibit fasting hypoglycaemia, reduced blood glucose and reduced circulating glucagon during intraperitoneal glucose tolerance testing. Processing of proglucagon and proinsulin is severely impaired in these mice [26,27]. Furthermore, supporting the notion of PC2 effects on proglucagon processing, we observed that the PCSK2 variant was associated with lower glucagon levels in hyperglycaemic individuals.…”
Section: Discussionsupporting
confidence: 71%
“…Heterozygotes display accelerated weight gain, glucose intolerance, and susceptibility to diet-induced obesity (7,37). PC2-null mice exhibit microsomia at birth, catch-up growth after birth, lipodysgenesis, glucose tolerance, and dietinduced obesity resistance as adults (8,38). It therefore appears that the two enzymes are the ying and yang of body mass and energy homeostasis, with PC1/3 playing a restraining role and PC2 playing a promoting one.…”
Section: Functional Overlap and Complementary And Opposing Roles Of Pmentioning
confidence: 99%
“…Interestingly, absence of PCSK2 is associated with pancreatic alpha cell hyperplasia and dramatic accumulation of proglucagon in these cells (Zhu et al, 2002). This pancreatic prohormone is alternatively processed to GLP-1 by PCSK1 (Webb et al, 2004), leading to markedly increase of the plasma levels of this peptide and other proglucagon-processing intermediates (Anini et al, 2010). The fasting plasma levels of GLP-like immunoreactivity in WT mice were greater for GLP-2 (0.7-0.8 ng/ml) than for GLP-1 (10-15 pg/ml).…”
Section: Grams Of Foodmentioning
confidence: 96%
“…Cellular expression of CCK, GLP-1, NPY and SS has been shown to be altered in PCSK2-KO mice (Anini et al, 2010;Furuta et al, 1997;Miller et al, 2003;Rehfeld et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation